A highly selective and sensitive chemosensor for l-tryptophan by employing a Schiff based Cu(ii) complex. (5th February 2018) - Saini, Anoop Kumar; Saraf, Mohit; Kumari, Pratibha; Mobin, Shaikh M.
Abstract : Construction of a new Cu(ii ) complex (1 ) based modified glassy carbon electrode (1-GCE ) for highly selective and sensitive detection ofl -tryptophan (l -Trp). Abstract : A new Cu(ii ) complex C40 H38 N4 CuO2 (1 ) was synthesized and characterized by elemental analysis, mass spectrometry and also authenticated by single crystal X-ray studies. Structural analysis of1 reveals the distorted square planar geometry around the Cu(ii ) centre and the presence of C–H⋯O and N–H⋯π hydrogen bonding interactions. The sensing behaviour of1 towardsl -tryptophan (l -Trp) was identified by UV-vis spectroscopic and cyclic voltammetry experiments. In the UV titration of1 withl -Trp, four distinct isosbestic points were observed. Furthermore, on modifying the surface of the glassy carbon electrode (GCE) by1 (1-GCE ) the oxidation potential ofl -Trp at +0.32 V is revealed, which is considerably lower than the values previously reported for other electrodes. Additionally, the1-GCE can detectl -Trp with a noteworthy detection limit (185 nM), sensitivity (3.156 μA μM −1 cm −2 ) and with distinguished selectivity in the presence of various other amino acids. The1-GCE also displays excellent reproducibility, repeatability and long term stability. Finally, electrochemical impedance spectroscopy (EIS) investigations were carried out to gauge the effects of modification with1 on the characteristics of the GCE. Moreover, the molecular docking study of1 with various proteins reveals the π–π stacking interaction withl -Trp.